HUBUNGAN KOMPETENSI PERAWAT GAWAT DARURAT DENGAN KINERJA PERAWAT DI INSTALASI GAWAT DARURAT (IGD) RSUD dr. H. MOHAMMAD ANWAR SUMENEP DAN RSUD SAMPANG - Dian Ika Puspitasari; Edi Widjajanto; Ika Setyo Rini (Wiraraja Medika : Jurnal Kesehatan, 2015)
Emergency department (ED) is initial services in hospital. Nurse on ED must have more capability than nurse in other department. Nurse in ED have to be fast, skilled and ready every time. Patient criteria in ED make nurse have to understand wide range of nursing competency. Competency including work readiness and work behaviour. Nurse’s competency related to work capability so can be use to predict nurse performance. The purpose of this study is to know relationship between emergency nurse’s competency with nurse’s performance in Emergency Department RSUD dr. H. Moh. Anwar Sumenep and RSUD Sampang. The design of this study is  correlational analytic with cross sectional approach. Purposive sampling was used as sampling technique so the participant became 30 nurse. Pearson correlation results indicate that there is a relationship between emergency department nurse competency based on diagnostic function (p value = 0.014), implementation of therapeutic intervention (p value = 0,020) and organizing the work roles (p value = 0.005) with the nurse performance. Emergency nurse competencies which is not related to nurse performance are effective management (p value = 0.890) and the role of helper (p value = 0.056). Correlation confounding variables results showed that there is a relationship between compensation (p value = 0.044) and work environment (p value = 0.037) with nurse performance. Based on the multiple linear regression analysis with backward method shows the most dominant competence that affect nurse performance is implementation of therapeutic intervention and the organizing work roles (52.4%). Confounding variables that greatly affect the nurse performance are working environment (14.7%). Nurse that usually applying skill on emergency nurse competencies will be more competent on doing their nursing skill for patient, and then nurse’s performance become better.   Keywords: Nurses competencies, Nurse performance, Emergency Department (ED)